2021
DOI: 10.1073/pnas.2023647118
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 inhibition elicits mitochondrial ROS to block intracellular bacterial colonization

Abstract: Mitogen-activated protein kinase kinase kinase 7 (MAP3K7), known as TAK1, is an intracellular signaling intermediate of inflammatory responses. However, a series of mouse Tak1 gene deletion analyses have revealed that ablation of TAK1 does not prevent but rather elicits inflammation, which is accompanied by elevation of reactive oxygen species (ROS). This has been considered a consequence of impaired TAK1-dependent maintenance of tissue integrity. Contrary to this view, here we propose that TAK1 inhibition–ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…TAK1 deficiency induced increase of ROS and cell death in keratinocytes, intestinal epithelial cells, and bone marrow-derived macrophages. [48] , [49] , [50] In the present study, we found that TAK1 deficiency caused accumulation of ROS in hepatocytes, contributing to hepatocytes ferroptosis. Different types of cell death can cause different extents of immune and inflammatory responses.…”
Section: Discussionsupporting
confidence: 54%
“…TAK1 deficiency induced increase of ROS and cell death in keratinocytes, intestinal epithelial cells, and bone marrow-derived macrophages. [48] , [49] , [50] In the present study, we found that TAK1 deficiency caused accumulation of ROS in hepatocytes, contributing to hepatocytes ferroptosis. Different types of cell death can cause different extents of immune and inflammatory responses.…”
Section: Discussionsupporting
confidence: 54%
“…It has recently been reported that TAK1-inhibition-induced cell death is mediated by RIPK1 activation, which triggers downstream programmed cell death pathways, including apoptosis and pyroptosis ( Geng et al, 2017 ; Jaco et al, 2017 ). This cell death-inducing mechanism is considered to be a host defense strategy against pathogens, which are capable of inhibiting components of inflammatory pathways, such as TAK1, MAP kinases and NF-κB ( López-Pérez et al, 2021 ; Orning et al, 2018 ; Paquette et al, 2012 ). Although cell death-mediated removal of infected cells is an efficient strategy to fight against pathogens, non-proliferating cells including neurons, cannot be replaced once they are dead, and their loss is detrimental to the host.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Moreover, a study has shown that inhibition of TAK1 in macrophages induces an increase in mitochondrial reactive oxygen species, which contributes to the abolishing of intracellular Salmonella colonization. 18 However, the potential function of TAK1 in Leishmania infection remains unclear thus far. In this study, we found that macrophage-specific deletion of TAK1 led to the inability of mice to mount an effective Th1 response, while the resultant high expression of IL-4 and arginase 1 (Arg1) led to a decrease in NO generation, thereby increasing the susceptibility of the host to Leishmania infection.…”
Section: Introductionmentioning
confidence: 99%